The assessment of electrospun scaffolds fabricated from polycaprolactone with the addition of L-arginine - Horakova, Jana; Oulehlova, Zuzana; Novotny, Vit; Jencova, Vera; Mikes, Petr; Havlickova, Kristyna; Prochazkova, Renata; Heczkova, Bohdana; Hadinec, Pavel; Sehr, Silvia; Wendel, Hans-Peter; Bell, Carl-Martin; et al. (Biomedical physics & engineering express, 2020)
Polycaprolactone (PCL) was electrospun with the addition of arginine (Arg), an α-amino acid that accelerates the healing process. The efficient needleless electrospinning technique was used for the fabrication of the nanofibrous layers. The materials produced consisted mainly of fibers with diameters of between 200 and 400 nm. Moreover, both microfibers and beads were present within the layers. Higher bead sizes were observed with the increased addition of arginine. The arginine content within the layers as well as the weight of the resultant electrospun materials were enhanced with the increased addition of arginine to the electrospinning solution (1, 5 and 10 wt%). The PCL + 1% Arg nanofibrous layer contained 5.67 ± 0.04% of arginine, the PCL + 5% Arg layer 22.66 ± 0.24% of arginine and the PCL + 10% Arg layer 37.33 ± 0.39% of arginine according to the results of the elemental analysis. A high burst release within 5 h of soaking was recorded for the PCL + 5% and PCL + 10% nanofibrous layers. However, the release rate of arginine from the PCL + 1% Arg was significantly slower, reaching a maximum level after 72 h of soaking. The resulting materials were hydrophobic. Hemocompatibility testing under static conditions revealed no effect on hemolysis following the addition of arginine and the prolongation of the prothrombin time with the increased addition of arginine, thus exerting an influence on the extrinsic and common pathway of coagulation activation. The results of the dynamic hemocompatibility assessment revealed that the numbers of blood cells and platelets were not affected significantly by the various electrospun samples during incubation. The TAT, β-thromboglobulin and SC5-b9 concentrations were characterized by a moderate increase in the PCL group compared to those of the control group. The presence of arginine resulted in a decrease in the investigated hemocompatibility markers. The PMN elastase levels were comparable with respect to all the groups.
Keywords: tkáňové podpůrné struktury; nanovlákna; biokompatibilní materiály; Wound Healing; elektřina; Arginine; hemolýza; lidé; tkáňové inženýrství; Nanofibers; Electricity; Polyesters; Biocompatible Materials; Materials Testing; Prothrombin Time; protrombinový čas; hojení ran; testování materiálů; Hemolysis; arginin; Tissue Engineering; polyestery; Tissue Scaffolds; Humans